Environmental conditions and marine heatwaves influence blue whale foraging and reproductive effort. Issue 2 (26th February 2023) - Barlow, Dawn R.; Klinck, Holger; Ponirakis, Dimitri; Branch, Trevor A.; Torres, Leigh G.
Abstract: Animal behavior is motivated by the fundamental need to feed and reproduce, and these behaviors can be inferred from spatiotemporal variations in biological signals such as vocalizations. Yet, linking foraging and reproductive effort to environmental drivers can be challenging for wide‐ranging predator species. Blue whales are acoustically active marine predators that produce two distinct vocalizations: song and D calls. We examined environmental correlates of these vocalizations using continuous recordings from five hydrophones in the South Taranaki Bight region of Aotearoa New Zealand to investigate call behavior relative to ocean conditions and infer life history patterns. D calls were strongly correlated with oceanographic drivers of upwelling in spring and summer, indicating associations with foraging effort. In contrast, song displayed a highly seasonal pattern with peak intensity in fall, which aligned with the timing of conception inferred from whaling records. Finally, during a marine heatwave, reduced foraging (inferred from D calls) was followed by lower reproductive effort (inferred from song intensity). Abstract : Our work links animal behavior and oceanography to provide insights into species life history and investigate the impacts of environmental change. We examine environmental correlates of blue whale vocalization patterns in Aotearoa New Zealand. Our results demonstrate the vulnerability of marine predator populations to marine heatwaves due to the links between environmental factors that control prey availability, foraging effort, and reproductive effort.